The Impact of Health Care Economics on Surgical Education - Margolin, David A. (Clinics in Colon and Rectal Surgery, 2012)
Just like the world economy in 2012, health care is in a state of flux. The current economic environment will impact not only current colorectal surgery residents, but also future generations of surgical trainees. To understand the economic impact of the current health care environment on colorectal surgery residencies, we need to know the basics of graduate medical education (GME) funding for all residents. Since the 1960s with the initiation of Medicare, the federal government through the Center for Medicare and Medicaid Services (CMS) has been the largest source of GME funding. There are two types of costs associated with GME. Direct GME (DME) funding covers costs directly attributed to the training of residents. These costs include residents' stipends, salaries, and benefits; cost of supervising faculty; direct program administration costs; overhead; and malpractice coverage. Indirect GME (IME) costs are payments to hospitals as an additional or add-on payment for the increased cost of care that is generally found in teaching hospitals. In 2010, President Barak Obama signed into law H.R. 3200, the Patient Protection and Affordable Care Act (PPACA). In 2011, the Supreme Court held that the majority of the PPACA is constitutional. Although the true impact of this bill is unknown, it will change the formula for Medicare GME reimbursement as well as shift unused residency positions to primary care.
Keywords: graduate medical education; funding; GME costs